The 2020s Global Crises: A Discussion of How International Institutions are Responding to the Russia-Ukraine Crisis and Climate Change Crisis - Mbah, Ruth Endam; Mbah, Emmanuel Fonjindam; Hultquist, Laura; Repp, Rande (Advances in Social Sciences Research Journal, 2023)
Humanity in the early 2020s has been endangered by several global crises like poverty, geopolitical unrest, inflation, pandemics, deepening inequality, supply-chain disruptions, climate change, and the Russia-Ukraine War; just to mention a few. The need for a social construct through the intervention of international institutions and non-state actors than individual state actors as postulated by Constructivists is essential. The purpose of this study is to review the response of various international organizations (IMF, World Bank, EU, UN, OECD, and NATO) to the global crises plaguing our world; specifically, Russia-Ukraine and Climate Change. We review the varied responses to the global impacts of the Russia-Ukraine war and Climate Change through the lens of Social Constructivism, an International Relations Theory. This theory emphasizes the impact of our actions on the world we live in and hence, the need for ‘rules’ that can guide our actions as well as reward those who follow the rules and punish those who do not. It also postulates the importance of international organizations/non-state actors in inducing our behaviors by lobbying or coaxing rather than individual state actors. Borrowing from the tenets of this theory, it is evident that our world needs the collaborative action of states through international relations and not individual state responses to combat these current global crises. This collaborative strategy is evident via the various responses (sanctions, emotional, material, weaponry) from the different international institutions listed in this study to the Russia-Ukraine war. Moreso, there continue to be diverse progressive collaborative conferences and policy reviews by member states of each of the international institutions listed in this study in response to the overwhelming impact of climate change. Even though this study focuses on international institutions' responses to just two of the global crises, there is an avenue for further review-research on the other crises.